Cardiopulmonary Resuscitation Management for Sudden Cardiac Arrest on Field Sport Activity - Arni Kusuma Dewi; Cahyaning Retno Indriani Santosa; Firazanti Firdaus Wahyu Putri; Maulana Taufikul Hakim; Rega Sugandi Putri; Aisha Muhti Jannata; Maria Tektonika Wardhani; Meilysan Sintikhe Rut Permatasari; Ervina Ayu Permata Sari (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Sudden cardiac arrest (SCA) is the most common cause of sudden death in athletes, accounting for 75% of all deaths during activity and sports. In order to preserve athletes' lives, cardiopulmonary resuscitation (CPR) and on-site defibrillation with an Automated external defibrillator (AED) should be undertaken immediately. Thus, observers ought not to hesitate in performing cardiac compression to restore circulation. Aim: to increase the number of coaches or teams commencing CPR and so improve the opportunities of survival after sudden cardiac arrest. Material and Methods: By collecting a total of ten studies, this article implements a literature review methodology to evaluate CPR administration in occurrences of SCA among field athletes. CPR administration, on-field sports, SCA, and athletes as subjects are the study's main objectives. Results: In accordance with the study's results, administering AEDs earlier is more effective. The majority of cardiac arrests in the field aren't treated immediately and accurately, which leads to fatalities. Because a cardiac arrest occurring during the first 10 minutes is critical for the athlete's survival, each minute lowers the athlete's chances of surviving by 7-10%. Conclusion: SCA in athletes is a serious medical condition that frequently results in death. To save athletes' lives, CPR and on-site defibrillation using an AED must be performed immediately.